Enzymatic Reetherification in the Production of Butterfat Substitutes - Tereshchuk L.; Starovoytova K. (Техника и технология пищевых производств)
Enzymatic reetherification of fats has numerous technological and economic advantages, which makes its large-scale implementation highly efficient. Unlike chemical modification, enzymatic reetherification demonstrates a greater specificity, typical of the catalytic action of lipase, and a higher controllability. Lipases with positional specificity cause redistribution of fatty acids to occur only in extreme provisions of triglycerides. In addition, this method is 1.5 times lower than hydrogenation of fats. The authors used the facilities of an innovative laboratory provided by JSC Eurasian Foods Corporation to conduct practical research on reetherification of fatty mixes. The main objective was to study the effect of the fats obtained by fermental reetherification on the quality indicators of butterfat substitutes. The research featured the input products to be used in the formula of reetherified fat and prepared fat mixes for butterfat substitutes. The paper describes the process of enzymatic reetherification of mixes of oils and fats, prepared reesterified fats, and buttermilk substitutes obtained from reetherified fats. The process involved a sequence of reactors filled with Lipozyme TL IM, a granulated substance of a microbic 1.3-specific lipase. The lipase was obtained from Thermomyces Lanuginosus, which had been immobilized with silica gel. The obtained products conformed to the butterfat standards in that they contained 16–2% of polynonsaturated fatty acids, no transisomers of fatty acids, ≤ 38% of palmitiny acid, and ≤ 5% of solid triglycerides at 35 of °C. The melting temperature was under body heat. The resulting characteristics of butterfat substitutes make them high-quality dairy products.